IMPLEMENTASI PERATURAN DAERAH KABUPATEN BANYUWANGI NOMOR 11 TAHUN 2014 TENTANG KETERTIBAN UMUM DAN KETENTRAMAN MASYARAKAT TERHADAP UPAYA PENEGAKAN HUKUM PENYELENGGARAAN MENARA TELEKOMUNIKASI DI WILAYAH KABUPATEN BANYUWANGI: (Studi Penelitian Pada Dinas Satpol PP Kabupaten Banyuwangi) - Sulaiman Utama, Rizki; Pasaribu, Agnes; Kurniawan Soetijono, Irwan (Fakultas Hukum Universitas 17 Agustus 1945 Banyuwangi, 2023)
Implementation Of Regional Regulation Of Banyuwangi Regency Number 11 Of 2014 Concerning Publicorder And Community Treatment Towards Efforts Enforcement Of Law Enforcement Telecommunication Tower In The Region Banyuwangi District (Research Study At The Banyuwangi Regency Satpol Pp Service) The presence of telecommunications towers is certainly very influential on national development. Moreover, by taking into account the needs of the community, the operation of telecommunication towers is growing very rapidly. However, what happens in the operation of telecommunications towers is not in accordance with the applicable provisions, so it does not meet all the requirements that must be met. The formulation of the problem in this research is: How is the implementation of the Banyuwangi Regency Regulation Number 11 of 2014 concerning Public Order and Public Peace on the legal protection of the people who live around telecommunications towers? and What are the law enforcement efforts carried out by the Civil Service Police Unit of Banyuwangi Regency against violations in the operation of telecommunications towers?. The type of research used in writing this thesis includes empirical legal research, which is a study that seeks to identify the laws that exist in society with the intention of knowing other symptoms. This study uses a factual approach and a statutory approach related to legal protection efforts for the people who live around telecommunications towers in the Banyuwangi Regency area. The results of the study concluded that the implementation of Banyuwangi Regency Regulation Number 11 of 2014 concerning Public Order and Community Peace in providing legal protection to citizens living around telecommunications towers still does not provide full guarantees. The lack of public awareness of their rights and obligations that should be fulfilled by the organizers is neglected. Thus, various efforts have been made by the Banyuwangi Regency Civil Service Police Unit in overcoming violations of telecommunications tower operations in the Banyuwangi Regency area by conducting socialization, supervision and control as well as law enforcement in order to provide legal awareness to community members who live around telecommunications towers and tower operators. telecommunications to comply with all applicable laws and regulations.